Procedure to Evaluate Current Formation Pressure in Wells with ESP - A. Gribennikov, O; N. Balandin, L; I. Astafev, V (International Journal of Engineering and Technology, 2018)
While operating the wells with ESP itâ€™s impossible to make the direct measurement of the formation pressure with the use of bottom-hole pressure gauge. That is why they presently use various indirect methods to evaluate formation pressure that are based upon the re-calculation of static fluid level in well annulus for the fluid column pressure. The authors consider the procedure to evaluate formation pressure that was designed for the wells equipped with ESP. This procedure is a simple one and enables to perform real-time formation pressure metering. The obtained results have been compared with hydro-dynamic studies and have demonstrated their high convergence.Â Â